ELABORAÇÃO DE E-BOOK FACILITADOR PARA A REDAÇÃO DE PATENTES - ABREU, LEANDRO RAFAEL DE (2020)
Based on the difficulty on the part of researchers in patent writing, this study aims to present a practical guide to assist researchers, inventors, university students, entrepreneurs or interested parties in writing a patent application in accordance with INPI rules. The preparation of the guide took into account the guidelines related to difficulties encountered in courses taught by an NIT and was prepared based on the Industrial Property Law and INPI in effect: IN/DIRPA n° 30/2013 and IN/DIRPA n° 31/2013. To develop the digital educational material, a practical guide with visual identity was developed, which is easy to understand in the e-book format. In addition, it is intended to contribute to reducing the problems faced by the patent bank's backlog in Brazil, which can be helped by filing a patent application that presents a clear wording. As a form of validation, the e-book was analyzed and evaluated by some researchers who answered a questionnaire and contributed to the construction and improvement of the guide. As a result, a practical guide was obtained, for wide use that can be used in courses and by any researcher. With that, the proposal of this work was reached, which was the availability of the guide, in the form of an e-book, permanently on the websites of Innovation Agencies, and it can be used by inventors and researchers from all over the country for free.